2010
DOI: 10.1007/s10517-010-1035-8
|View full text |Cite
|
Sign up to set email alerts
|

Hemorheological Effects of Ortho-Isobornyl Phenol Derivative under Conditions of Brain Ischemia in Rats

Abstract: Hemorheological activity of 4-methyl-2,6-di-isobornyl phenol, a new o-isobornyl phenol derivative, was studied under conditions of experimental prolonged partial cerebral ischemia. Brain ischemia is associated with hemorheological disorders which can be characterized as blood hyperviscosity syndrome: increased viscosity of the whole blood (within a wide range of shear rates), plasma viscosity, fibrinogen content in blood plasma, and platelet aggregation; deterioration of platelet deformability and reduced avai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 5 publications
0
3
0
3
Order By: Relevance
“…В интервале исследованных концентраций для соединений 1 и 5, ввиду их относительно невысокого ингибирующего действия, наряду с обрывом цепей окис-ления на молекуле АО имеет место также и квадратич-ный обрыв цепей. Поэтому для количественной оценки параметра ингибирования fk 7 , где f -стехиометрический коэффициент ингибирования, k 7 -константа скорости взаимодействия антиоксидантов с пероксирадикалами, который является характеристикой антирадикальной Таблица 1. Структурные формулы и значения параметра fk 7 соединений 1-8.…”
Section: экспериментальная частьunclassified
See 2 more Smart Citations
“…В интервале исследованных концентраций для соединений 1 и 5, ввиду их относительно невысокого ингибирующего действия, наряду с обрывом цепей окис-ления на молекуле АО имеет место также и квадратич-ный обрыв цепей. Поэтому для количественной оценки параметра ингибирования fk 7 , где f -стехиометрический коэффициент ингибирования, k 7 -константа скорости взаимодействия антиоксидантов с пероксирадикалами, который является характеристикой антирадикальной Таблица 1. Структурные формулы и значения параметра fk 7 соединений 1-8.…”
Section: экспериментальная частьunclassified
“…Во-первых, наличие объемного пор-фиринового заместителя в о-положении по отношению к гидроксильной группе фенола может обусловливать стерические затруднения при взаимодействии ОН-группы с пероксирадикалами. Во-вторых, электро-ноакцепторная амидная группа, обеспечивающая связь между фенольным и порфириновым фрагментами, может также способствовать уменьшению величины fk 7 . И, наконец, к снижению константы скорости взаимодей-ствия с пероксирадикалами может привести образование внутримолекулярной водородной связи [10,11,22] между фенольной гидроксильной группой и атомами азота или кислорода амидной группы (С=О···Н-О и N···Н-О).…”
Section: соединениеunclassified
See 1 more Smart Citation
“…In the experimental group, the rats received 100 mg/ kg dibornol in starch gel once a day for 3 days before and 5 days after ischemia/reperfusion (therapeutic and prophylactic scheme of drug administration). The dose and mode of dibornol administration were justifi ed by earlier fi ndings on pharmacokinetics and pharmacodynamics of the drug [6]. Sham-operated rats and controls received starch gel according to the same scheme.…”
Section: Methodsmentioning
confidence: 99%
“…Our previous studies demonstrated its hemorheological, antiplatelet, and antithrombogenic effects within the settings of the model of transient cerebral ischemia [4,5]. At present, we are carrying out a comprehensive study of the cardioprotective activity of the drug [6,7].…”
Section: Introductionmentioning
confidence: 99%